Chitin Determination in Residual Streams Derived From Insect Production by LC-ECD and LC-MS/MS Methods - Nurfikari, Azkia; de Boer, Wietse (Frontiers in Sustainable Food Systems, 2021)
Chitin, a biopolymer present in fungi and arthropods, is a compound of interest for various applications, such as in the agricultural and medical fields. With the recently growing interest in the development of insect farming, the availability of chitin-containing residual streams, particularly the molting skins (exuviae), is expected to increase in the near future. For application purposes, accurate quantification of chitin in these insect sources is essential. Previous studies on chitin extraction and quantification often overlooked the purity of the extracted chitin, making the outcomes inconsistent and prone to overestimation. The present study aims to determine chitin content in the exuviae of three insect species mass-reared worldwide: black soldier fly (BSF), mealworm, and house cricket. Chitin was chemically extracted using acid and alkali treatments to remove minerals and proteins. The purity of extracted chitin was evaluated by hydrolyzing the chitin into glucosamine, followed by quantitative determination of the latter using two liquid chromatography methods: electrochemical detection (ECD) and tandem mass spectrometry (MS/MS). Both methods proved accurate and precise, without the need for labor-intensive derivatization steps. Pearson's correlation and Bland-Altman plots showed that the glucosamine determination results obtained by the two methods were comparable, and there is no consistent bias of one approach vs. the other. The chitin content in extracted residues ranged between 7.9 and 18.5%, with the highest amount found in BSF puparium. In summary, the study demonstrated that (1) the residual streams of the insect farming industry have a great potential for utilization as an alternative chitin source, and (2) both LC-ECD and LC-MS/MS are reliable for the quantitative determination of glucosamine in insect chitin.